2017
DOI: 10.1183/13993003.01339-2016
|View full text |Cite
|
Sign up to set email alerts
|

Acute exacerbations in the INPULSIS trials of nintedanib in idiopathic pulmonary fibrosis

Abstract: Time to first investigator-reported acute exacerbation was a key secondary end-point in the INPULSIS trials of nintedanib in patients with idiopathic pulmonary fibrosis (IPF).We used the INPULSIS trial data to investigate risk factors for acute exacerbation of IPF and to explore the impact of nintedanib on risk and outcome of investigator-reported and adjudicated confirmed/suspected acute exacerbations. Mortality following these events and events adjudicated as not acute exacerbations was analysed using the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
2
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 23 publications
9
96
2
7
Order By: Relevance
“…Acute exacerbations of IPF (identified using different methodologies) were reported in 2-16% of placebo-treated patients over 24-60 weeks, while mortality ranged from 2.5-13.3% over approximately 28-96 weeks [16,[18][19][20][21][22][23][24][25][26][30][31][32][33]. Data from the INPULSIS trials suggests that events adjudicated as confirmed or suspected acute exacerbations were associated with similar post-event mortality as other forms of acute respiratory worsening [68]. This supports the perspective of an international working group that the requirement for an event to be idiopathic should be removed from the definition of an acute exacerbation [5].…”
Section: Lessons Learned On the Natural History Of Idiopathic Pulmonamentioning
confidence: 99%
“…Acute exacerbations of IPF (identified using different methodologies) were reported in 2-16% of placebo-treated patients over 24-60 weeks, while mortality ranged from 2.5-13.3% over approximately 28-96 weeks [16,[18][19][20][21][22][23][24][25][26][30][31][32][33]. Data from the INPULSIS trials suggests that events adjudicated as confirmed or suspected acute exacerbations were associated with similar post-event mortality as other forms of acute respiratory worsening [68]. This supports the perspective of an international working group that the requirement for an event to be idiopathic should be removed from the definition of an acute exacerbation [5].…”
Section: Lessons Learned On the Natural History Of Idiopathic Pulmonamentioning
confidence: 99%
“…As expected, the risk of idiopathic acute exacerbations was higher in patients with more advanced disease in the INSTAGE trial than in patients in the INPULSIS trials. A wealth of data has demonstrated that low FVC and/or low DLco are risk factors for acute exacerbations in patients with IPF [11,32,33], possibly because patients with more advanced disease are more vulnerable to insults such as infection that may lead to an acute exacerbation [11]. Similarly, the risk of mortality was higher in patients with more severe impairment in DLco in the INSTAGE trial than in patients in the INPULSIS trials, consistent with previous studies identifying low DLco as a risk factor for mortality in patients with IPF [4,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Collard et al . have previously published a risk factor analysis on time to first acute exacerbation also using data from the INPULSIS trials.…”
Section: Discussionmentioning
confidence: 99%
“…9 Nonetheless, our analysis indirectly supports an effect of nintedanib treatment on the exacerbation risk as nintedanib has been shown to reduce the annual rate of FVC decline significantly. 5 Collard et al 25 have previously published a risk factor analysis on time to first acute exacerbation also using data from the INPULSIS trials. Their final Cox proportional hazard model included baseline %pFVC, supplemental oxygen, use of antacid medications, and randomization to nintedanib as risk factors for investigator-reported acute exacerbations.…”
Section: Time-to-event Model For Ipf Exacerbationsmentioning
confidence: 99%